Delusions in informatics education - Szlávi, Péter; Zsakó, László (Teaching Mathematics and Computer Science, 2004)
In the following article our intention is to try to introduce the negative ideas that exist today in Hungary regarding informatics education within the secondary education system. [Zs] As far as we know, these delusions are characteristic of not only Hungary, but we believe that we should look for our own mistakes, that is why we refer to Hungarian examples.We have examined the informatic knowledge taught in the first 10 years of secondary education, the possible curriculum of the general informatics subject.To reach our aim, first we have to deviate a bit from our original topic, because without this, it would be more difficult to understand the core subject of the article. In the deviation we will explain what is called informatics, what is called informatics subject. Then we will deal with the main topic and in the summary we will explain what we believe is the aim of general informatics education.